2008
DOI: 10.1208/s12249-008-9144-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbopol-Based Gels for Nasal Delivery of Progesterone

Abstract: Abstract. The purpose of this study was to investigate the nasal absorption of progesterone from carbopol-based nasal gels in rabbits. Progesterone nasal gels were prepared by dispersing carbopol 974 (1%, 1.5%, and 2%) in distilled water followed by addition of progesterone/progesterone-β cyclodextrin complex dissolved in propylene glycol then neutralization. The potential use of β cyclodextrin (CD) as nasal absorption enhancer by simple addition, as a physical mixture and as a complex with progesterone was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…The aim of the present work was to provide new information about the structure of the Carbopol 974P NF (C974P), the oral pharmaceutical grade of the carbomers, which has been only little addressed in the literature to date. The C974P is used in many oral and mucosal contact applications such as controlled release tablets, oral suspension, and bioadhesive formulations . The C974P is cross‐linked with allyl pentaerythritol, but no precise information about the degree of cross‐linking is available to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present work was to provide new information about the structure of the Carbopol 974P NF (C974P), the oral pharmaceutical grade of the carbomers, which has been only little addressed in the literature to date. The C974P is used in many oral and mucosal contact applications such as controlled release tablets, oral suspension, and bioadhesive formulations . The C974P is cross‐linked with allyl pentaerythritol, but no precise information about the degree of cross‐linking is available to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, increased permeability of the nasal mucosa by DMβCD could also improve the absorption of the drug, since numerous studies have demonstrated the efficient nasal permeation enhancing effect of cyclodextrin for different drugs (13). Lastly, since Carbopol 940 could increase the viscosity of the formulation and form a hydrogen bond with the nasal mucosa, this also resulted in increased nasal residence time of the formulation and thus improved bioavailability (14).…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…An N-acylated amino acid was used during the reaction to prevent the occurrence of unwanted side reactions resulting in the formation of oligo/poly cysteine conjugates [27]. After lyophilisation, all polymer conjugates appeared as white, powders of fibrous structure which were readily soluble over a wide pH range (3)(4)(5)(6)(7)(8). The mean percentage yield (n=3) of Paa-NAC and QPaa-NAC conjugates were estimated at 68.8 ± 2.8% and 73.6 ± 2.3 % respectively, while the percentage yield of the Paa-TBA and QPaa-TBA conjugates was estimated at 73.1 ± 4.4% and 83.6 ± 7.7 %, respectively.…”
Section: Validation Of Polymer Synthesismentioning
confidence: 99%
“…This mucoadhesive process extends the residence time of the dosage form at the application site allowing adequate time for polymers that enhance mucosal wall permeation to exert their effect while also creating a steep concentration gradient which facilitates the process of passive diffusion necessary for optimal drug absorption [4,5]. Polymers which have been used successfully in mucoadhesive dosage form design include chitosan, polyacrylic acid and alginate [2,6,7,8]. Their distinctive mucoadhesive property has been attributed to the availability of charged functional groups within their structure which are able to foster ionic/electrostatic interaction with components of mucin .…”
mentioning
confidence: 99%